2011
DOI: 10.1007/s00408-011-9321-4
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics and Prognosis of Nontuberculous Mycobacterial Lung Disease with Different Radiographic Patterns

Abstract: In Taiwan, NTM-LD patients with consolidative pattern have the worst prognosis while patients with cavitary pattern have worse survival than those with bronchiectasis in MAC-LD. Because varying radiographic patterns represent different prognoses, understanding the characteristics of NTM-LD patients with different radiographic patterns complements clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
1
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 22 publications
1
47
1
4
Order By: Relevance
“…Shu et al have reported that the 6-month survival in NTM patients with lung lesion is poor based on a single hospital study. The survival is particularly poor for those with worsening consolidation and cavitation of lung [33]. An earlier study found that 72% of patients with lung consolidation suffered from ARF [4].…”
Section: Discussionmentioning
confidence: 99%
“…Shu et al have reported that the 6-month survival in NTM patients with lung lesion is poor based on a single hospital study. The survival is particularly poor for those with worsening consolidation and cavitation of lung [33]. An earlier study found that 72% of patients with lung consolidation suffered from ARF [4].…”
Section: Discussionmentioning
confidence: 99%
“…At a hospital in Taipei City, Northern Taiwan, the annual prevalence of NTM PD increased from 1.28/100,000 in 2000, to 7.94/100,000 in 2008 (73). From the same institution, 252 NTM PD patients with classifiable radiographic patterns (cavitary, bronchiectatic, or consolidative) were identified over 2007–2009 (74). The mean age was 63.7 years and 50.8% were men (74).…”
Section: East Asiamentioning
confidence: 99%
“…From the same institution, 252 NTM PD patients with classifiable radiographic patterns (cavitary, bronchiectatic, or consolidative) were identified over 2007–2009 (74). The mean age was 63.7 years and 50.8% were men (74). The studies from Taiwan identified NTM PD patients as being in the same age range as most other studies.…”
Section: East Asiamentioning
confidence: 99%
“…This has been reflected in successive guidelines which recommend more aggressive treatment of fibrocavitary disease [5]. Other patterns of disease have been reported, in particular consolidation and infiltrative patterns have been associated with poor outcomes [911] however with no agreed consensus regarding definitions for these patterns, the findings remain unique to the individual studies. Even when an additional ‘consolidative’ category was used, one study found that 27% of subjects still did not clearly fit any category [3] and another was still unable to classify the radiological appearances of 229/481 subjects [9].…”
Section: Discussionmentioning
confidence: 99%
“…NTM-pulmonary disease has been observed to commonly fall into two clinico-radiological patterns of disease, fibrocavitary and nodular-bronchiectatic disease, and this classification forms the basis of treatment recommendations in guidelines [5] and has important prognostic implications [68]. Whilst being of great clinical utility this division may not capture the spectrum of radiological appearances, some of which may not fit clearly into either group [3, 911]. …”
Section: Introductionmentioning
confidence: 99%